Особенности процесса ценообразования инновационных промышленных продуктов (Путеводитель предпринимателя, 2020)
In article the role of the prices and process of pricing in the market economy conditions is considered, factors of formation of market price are reflected, features of pricing for an innovative industrial output are revealed, the problem of research and practical use of modern methods of pricingfor an innovative industrial output in the conditions of high complexity and dynamism of economic processes is proved, parametrical methods and models of pricing, a condition and sphere of their application are studied.